Reliability analysis for vertical integration of protection, measurement, merge unit, and intelligent terminal device - Ying Li; Weiquan Wang; Liang Zhang; Zhujian Liang; Zhenli Xu; Yuansheng Liang (Global Energy Interconnection, 2023)
The reliability analysis of vertically integrated protection devices is crucial for designing International Electrotechnical Commission (IEC) 61850-based substations. This paper presents the hardware architecture of a four-in- one vertically integrated device and the information transmission path of each function based on the functional information transmission chain of protection devices, measurement and control devices, merging units, and intelligent terminals. Additionally, a reliability analysis model of the protection device and its protection system is constructed using the fault tree analysis method while considering the characteristics of each module of the vertically integrated device. The stability probability of the protection system in each state is analyzed by combining the state-transfer equations of line and busbar protection with a Markov chain. Finally, the failure rate and availability of the protection device and its protection system are calculated under different ambient temperatures using a 110 kV intelligent substation as an example. The sensitivity of each device module is analyzed.